Numerical Analysis of the Condensing Steam Flow by Means of ANSYS Fluent and in-House Academic Codes With Respect to the Capacity for Thermodynamic Assessment - Shabani, Sima; Majkut, Mirosław; Dykas, Sławomir; Wiśniewski, Piotr; Smołka, Krystian; Cai, Xiaoshu; Zhang, Guojie (Frontiers in Energy Research, 2022)
In this paper numerical analysis of the condensing steam flow in a converging-diverging nozzle is investigated. The ANSYS Fluent results are compared with the results of the in-house academic Computational fluid dynamics code with respect to the capacity for thermodynamic assessment. The “local” real gas equation of state is used as a mathematical complement of flow governing equations in the in-house code. In the Fluent code, the thermodynamic functions as well as the steam and water physical properties are calculated based on the IAPWS formulation with the use of the UDF. The condensation model with the Fuchs and Sutigin correction of the droplet growth equation and nucleation rate with the Kantrowitz correction is implemented in both CFD codes. The CFD results are compared with the obtained experimental data. The experiment was carried out using an in-house steam facility with a transonic steam tunnel. The investigated geometry is a converging-diverging nozzle as adopted under the International Wet Steam Experimental Project with the diverging section expansion rate of 3,000 s−1 and the total throat height of 40 mm.